Toward an efficient modeling of neutrino-driven winds in binary neutron star mergers. Issue Volume 16:Issue S363(2020) (June 2020) - Gizzi, Davide; Rosswog, Stephan; O'Connor, Evan; Perego, Albino; Lundman, Christoffer
Abstract: We present a mesh-free, neutrino transport approximation called Advanced Spectral Leakage, designed as a powerful tool for simulations of neutrino-driven winds in binary neutron star mergers with the Smoothed-Particle Hydrodynamics. We post-process a number of snapshots and compare relevant neutrino quantities with respect to computationally more expensive transport approaches. We find that the scheme recovers neutrino luminosities and mean energies within 25% accuracy and is computationally more efficient.